Rutting Prediction of Asphalt Mixtures Containing Treated and Untreated Recycled Concrete Aggregate (Journal of Engineering, 2024)
Rutting is a crucial element of the mechanical performance characteristics of asphalt mixtures, which was the primary target of this study. The task involved substituting various portions of virgin coarse aggregate with recycled concrete aggregate materials that had been treated or left untreated at rates ranging from 25 to 100%, with a constant increase of 25%. The treatment process of recycled concrete aggregate involved soaking in acetic acid, followed by a mechanical process for a short time inside a Los Angeles machine without the balls. This research utilized two primary tests: the standard Marshall test to identify the optimal asphalt contents and the volumetric characteristics of asphalt mixtures. The other one was the wheel tracking test, which involved manufacturing 11 slabs with a dimension of 30 x 40 × 5 cm and testing them under repeated wheel loads of 700 N at 55°C to investigate rutting resistance. The results demonstrate that using RCA had a negative impact on rutting resistance, where rut depth increased by 21.64% when using 100% pre-soaked treated RCA.